Transformation from Manual Medical Records to Electronic Medical Records: A Phenomenological Study - Hastin Atas Asih; Indrayadi Indrayadi (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
With the rapid advancement of information technology in the healthcare sector, the implementation of electronic medical records has become a dominating trend. The transition from manual medical records to electronic medical records is not just a technological transformation but also a revolution in healthcare services. This research aims to explore the hospital's experience in transitioning from manual medical records to electronic medical records at dr. R. Soeharsono hospital, a level iii hospital. This research utilizes a qualitative approach with a phenomenological design. Data collection is conducted through in-depth interviews, and data analysis follows the colaizzi method. Triangulation methods were carried out by means of interviews with electronic medical records users, document analysis, and field observations The study involves four participants. The results reveal four main themes: Benchmarking, Finding suitable service platforms, EMR facilities, EMR training and Implementation of EMR. Electronic medical records training emerges as a crucial factor in preparing for electronic medical records usage, supported by regulations mandating electronic medical records service platforms. The use of external service platforms is acknowledged as an effort to enhance data security. The success of the implementation of electronic medical records also relies on the availability of supporting facilities and the selection of the right service platforms. This research provides important insights for hospitals and related parties to understand the transformation process from manual medical records to electronic medical records optimally. Keywords: Electronic Medical Record, technology